The impact of Ureaplasma infections on pregnancy complications. Issue 1 (1st January 2020) - Bartkeviciene, Daiva; Opolskiene, Gina; Bartkeviciute, Agne; Arlauskiene, Audrone; Lauzikiene, Dalia; Zakareviciene, Jolita; Ramasauskaite, Diana
ABSTRACT: The aim of this study was to assess if ureaplasmas are associated with pregnancy complications and diseases in newborns. Pregnant women with complaints and threatening signs of preterm delivery were included. A sample, taken from the endocervical canal and from the surface of the cervical portion, was sent to the local microbiology laboratory for DNA detection of seven pathogens: Chlamydia trachomatis, Mycoplasma hominis, Mycoplasma genitalium, Ureaplasma parvum, Ureaplasma urealyticum, Neisseria gonorrhoeae, and Trichomonas vaginalis . The Pearson Chi-Square test was used to determine the difference in unpaired categorical data. A two-sided p value <0.05 was considered to be statistically significant. In all, 50 pregnant women with complaints and threatening signs of preterm delivery were included. Premature rupture of uterine membranes was found in 23 (46%) of the patients and 38 women (76%) had preterm delivery. Ureaplasma infections were associated with a premature rupture of membranes (p < 0.004), the placental inflammation (p < 0.025), a newborn respiratory distress syndrome (p < 0.019). Ureaplasmas could have affected the preterm leakage of fetal amniotic fluid and are associated with the placental inflammation and a newborn respiratory distress syndrome.